D & Dimsum Marketing Analysis of Purchasing Decisions and Word of Mouth - Hermawati, Dewi; Pristiyono, Pristiyono; Hutagaol, Anita Sri Rejeki (MID Publisher International, 2024)
The importance of marketing in a business, including for the D&Dimsum culinary business in attracting interest and purchasing decisions can be influenced by word of mouth. The purpose of this study was to determine the direct effect of product and promotion on purchasing decisions and word of mouth. The author's theoretical analysis uses a systematic literature review that is relevant to the research needs and a minimum sample size of 100 samples with an error rate of 5% with a simple random sampling technique. This study found that the percentage of research respondents' answers was dominated by answers agreeing to the product variable of 53.8%, the promotion variable of 47.2%, the purchase decision variable of 40.0% and the word of mouth variable of 41.4%. The research findings that local culinary products D & Dinsum from hypothesis testing that products and promotions directly have an influence on purchasing decisions and purchasing decisions directly have a relationship with word of mouth